Global dynamics for a class of infection-age model with nonlinear incidence - Li, Yuji; Xu, Rui; Jiazhe, Jiazhe (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, we propose an HBV viral infection model with continuous age structure and nonlinear incidence rate. Asymptotic smoothness of the semi-flow generated by the model is studied. Then we caculate the basic reproduction number and prove that it is a sharp threshold determining whether the infection dies out or not. We give a rigorous mathematical analysis on uniform persistence by reformulating the system as a system of Volterra integral equations. The global dynamics of the model is established by using suitable Lyapunov functionals and LaSalle’s invariance principle. We further investigate the global behaviors of the HBV viral infection model with saturation incidence through numerical simulations.